Cerebral Sinovenous Thrombosis in Neonates and Children - Melissa G. Chung (Pediatric Neurology Briefs Publishers, 2016)
Investigators from Erasmus University Hospital in Belgium and Gustave-Dron Hospital and Roger-Salengro Hospital in France studied the clinical and neuroradiologic characteristics of cerebral sinovenous thrombosis (CSVT) in neonates and children.